1986
DOI: 10.1128/aac.29.6.1059
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antibacterial activity of AM-833, a new quinolone derivative

Abstract: AM-833 showed potent activity against members of the family Enterobacteriaceae, Neisseria spp., and HaemophUus influenzae and good activity against staphylococci, Pseudomonas aeruginosa, and BranhameUa catarrhalis. Against these bacteria, its activity was roughly comparable to that of norfloxacin and ofloxacin but was slightly less potent than that of ciprofloxacin. This compound also showed good activity against drug-resistant strains such as methicillin-resistant Staphylococcus aureus and gentamicin-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
45
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 11 publications
3
45
0
Order By: Relevance
“…Also, C. freundii can rapidly acquire resistance to nalidixic acid; the MIC rose to 1,600 ,ug/ml after five transfers (8). We reported earlier that one of the resistance mechanisms of the spontaneous nalidixic acid-resistant mutant M2-5 was an altered DNA gyrase A subunit (1).…”
mentioning
confidence: 99%
“…Also, C. freundii can rapidly acquire resistance to nalidixic acid; the MIC rose to 1,600 ,ug/ml after five transfers (8). We reported earlier that one of the resistance mechanisms of the spontaneous nalidixic acid-resistant mutant M2-5 was an altered DNA gyrase A subunit (1).…”
mentioning
confidence: 99%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of outer membrane proteins demonstrated the appearance of a 54,000-dalton protein in the nfxB mutant. These findings suggested that the norfloxacin resistance mechanism in the nfxB mutant might be an alteration in outer membrane permeability to norfloxacin.Norfloxacin and other new 4-quinolones show potent antibacterial activity against gram-negative and grampositive bacteria (11,14,20). They also have high in vitro and in vivo antibacterial activity against Pseudomonas aeruginosa strains that show a strong intrinsic resistance to various antimicrobial agents including older quinolones such as nalidixic acid (11,20,42).…”
mentioning
confidence: 99%
“…Norfloxacin and other new 4-quinolones show potent antibacterial activity against gram-negative and grampositive bacteria (11,14,20). They also have high in vitro and in vivo antibacterial activity against Pseudomonas aeruginosa strains that show a strong intrinsic resistance to various antimicrobial agents including older quinolones such as nalidixic acid (11,20,42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A portion (about 5 [LI) of the dilution was inoculated with an inoculation apparatus (Microplanter; Sakuma Seisakusho, Tokyo, Japan) onto agar plates containing various concentrations of drug. The final inoculum size was approximately 104 CFU per spot.…”
mentioning
confidence: 99%